STANDAR PELAYANAN MINIMAL DI KANTOR CAMAT BATHIN SOLAPAN KABUPATEN BENGKALIS TAHUN 2017 - Suchairi, Risky; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Sub-Districts of Bathin Solapan is one of the sub-districts which was established on February 9, 2017 by the Government of Bengkalis District with the sub-district of Pinggir District, Office of Camat Bathin Solapan Bengkalis Regency still status of rent. at least at the Office of the Sub-district of Bathin Solapan Bengkalis Regency in 2017? ". The purpose of the research is to find out the minimum service standards at the Office of the Sub-district of Bathin Solapan in Bengkalis Regency in 2017. Qualitative research method.This research was conducted in sub-district Bathin Solapan. Primary data sources through interviews as well as secondary data sources through documents. Data analysis techniques carried out with qualitative descriptive analysis.After conducting the research, the results obtained and discussed as follows: the type of service in the Office Camat Bathin Solapan consists of 2 (two) types of services that is the service in the field of licensing and service in the field of non-licensing, service requirements in the Office Bathin Solapan Subdistrict there are different conditions in each but the conditions are easy to be completed by the community, the process / service procedure at the Office of the Bathin Solapan Sub-district from entering the file to the release of the documents the community wants to include information officers, file receiving officers, computer operators, general, sub-district secretary, and sub-district head, the officer responsible for the service at the Office of the Bathin Solapan Sub-district consists of the organizer officials, namely: sub-district head, sub-district secretary, and section head. And the technical service officers are: information officer, counter / recipient officer, and computer operator, service time at Bathin Solapan Subdistrict Office, there is a delay in completion of the document due to the limitations of the existing technical and equipment implementers, the cost of service at the Office of the Camat of Bathin Solapan is free or documents carried out by the community are not charged.Keywords: Minimum Service Standards, District Offices